2019
DOI: 10.1002/cae.22158
|View full text |Cite
|
Sign up to set email alerts
|

A data‐mining‐based approach to informed decision‐making in engineering education

Abstract: In outcome‐based academic programs, Program Educational Objectives (PEOs) and Student Outcomes (SOs) are two cores around which all programs’ components and processes revolve. Needless to say, the PEOs‐SOs mapping is very critical for program success and, therefore, a deep understanding of PEOs, SOs, and their intra/inter‐correlations is very important for effective program's decisions making. In this context, this paper proposes a data mining‐based approach to discover hidden knowledge of PEOs, SOs, and their… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 22 publications
2
10
0
Order By: Relevance
“…As students are the beneficiaries of higher education institutions, analyzing these transitional data based on the learning outcomes can provide a useful notion of the quality of education offered by the university. Also, an analysis of this trait can be useful in administrative planning and decision‐making of educational institutions' accreditation process that contributes to continuous quality improvement [17,28]. The academic data analysis related to the students will allow the institution to validate the achievement of specific learning outcomes [8].…”
Section: Results and Analysismentioning
confidence: 99%
See 2 more Smart Citations
“…As students are the beneficiaries of higher education institutions, analyzing these transitional data based on the learning outcomes can provide a useful notion of the quality of education offered by the university. Also, an analysis of this trait can be useful in administrative planning and decision‐making of educational institutions' accreditation process that contributes to continuous quality improvement [17,28]. The academic data analysis related to the students will allow the institution to validate the achievement of specific learning outcomes [8].…”
Section: Results and Analysismentioning
confidence: 99%
“…Fortunately, for this case study, the selected dataset is of good quality with no missing values. However, if the datasets have missing values and outliers, then they must be appropriately identified and processed [24,28]. Clustering is done using k-means and k-medoids techniques by taking the Euclidean distance using the RapidMiner tool.…”
Section: Data Preparation and Methodologymentioning
confidence: 99%
See 1 more Smart Citation
“…In this work the PEOs-SOs mapping data are collected from the SSRs of 215 engineering programs accredited by ABET-EAC between 2000 and 2019. It should be noted that collected raw data have been used by the authors in several previous pieces of research [29,30], and more details can be found in [31]. Figure 3 is a snippet of the PEOs-SOs data.…”
Section: Raw Data Collectionmentioning
confidence: 99%
“…Characterizations of the flipped-based teaching in classroom are discussed in many ways. Few of them focus on the usage of digital technology [7,8], few of them target social media [9], and few discuss the significance of applying a certain pedagogical way, like mastery-based learning [10] or cooperative learning method [11].…”
Section: Introductionmentioning
confidence: 99%